Reinforced behavioral variability: Working towards an understanding of its behavioral mechanisms. Issue 3 (12th October 2015) - Doughty, Adam H.; Galizio, Ann
Abstract: There is disagreement about how to characterize the environment‐behavior relations involved in the reinforcement of behavioral variability. The present research examined some of these issues using food‐maintained, 4‐peck sequences in pigeons. Experiment 1 evaluated the claim that behavioral variability is not reinforced directly but, rather, is the byproduct of changing over within sequences. Considerably higher levels of behavioral variation occurred under a relative‐frequency threshold contingency than under a contingency that required a changeover but not variability per se. These results are consistent with the argument that behavioral variability is reinforced directly. Experiment 2 assessed the effects on variation levels of manipulating inter‐trial and inter‐response intervals. Variability increased with longer inter‐response intervals but not with longer inter‐trial intervals. These results are consistent with multiple explanations, including the notion that remembering past behavior interferes with the emission of reinforced variation. Consequently, Experiment 3 examined more directly the relation between remembering and reinforced variation. Variation levels were not affected by a concurrent contingency that encouraged pigeons to remember their past behavior. The implications of this research are presented in the context of working towards an understanding of the environment‐behavior relations involved in the reinforcement of behavioral variability.